2010
DOI: 10.1007/s00268-010-0697-8
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Body Mass Index on Short‐Term and Long‐Term Outcome after Resection of Esophageal Cancer

Abstract: IntroductionCachexia and obesity have been suggested to be risk factors for postoperative complications. However, high body mass index (BMI) might result in a higher R0-resection rate because of the presence of more fatty tissue surrounding the tumor. The purpose of this study was to investigate whether BMI is of prognostic value with regard to short-term and long-term outcome in patients who undergo esophagectomy for cancer.MethodsIn 556 patients who underwent esophagectomy (1991–2007), clinical and pathologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
83
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(94 citation statements)
references
References 32 publications
9
83
2
Order By: Relevance
“…Operative approach (transhiatal vs. transthoracic) is also reported to be highly correlated to the development of pulmonary complications [2,20]. In accordance with other reports, the American Society of Anesthesiologists (ASA) score and BMI were not associated with treatment of pneumonia in our series [20,27]. …”
Section: Discussionsupporting
confidence: 80%
“…Operative approach (transhiatal vs. transthoracic) is also reported to be highly correlated to the development of pulmonary complications [2,20]. In accordance with other reports, the American Society of Anesthesiologists (ASA) score and BMI were not associated with treatment of pneumonia in our series [20,27]. …”
Section: Discussionsupporting
confidence: 80%
“…Grotenhuis et al 61. reported that BMI was not of prognostic value for short‐ and long‐term outcomes in patients who underwent esophagectomy for cancer and it is not an independent predictor for radical (R0) resection.…”
Section: Resultsmentioning
confidence: 99%
“…Our results may suggest that chest physical therapy stimulates lung expansion and improves lung ventilation, thereby preventing or eliminating the build-up of liquid in the pleural space, meeting the drainage removal criteria (less than 100 mL in 24 hours) earlier and facilitating the removal of the drain 21 . Re-intubation for respiratory failure in patients undergoing esophagectomy varies from 9% to 17% of the cases [22][23][24] . This frequency in our study has been lower (6.6%) in the control group and even lower in the PTG (2.5%), possibly due to protective effect of physical therapy intervention in this population, which had decreased significantly since the frequency of respiratory complications.…”
Section: Discussionmentioning
confidence: 99%